The legal regime of the International Criminal Court : essays in honour of Professor Igor Blishchenko : in memoriam Professor Igor Pavlovich Blishchenko (1930-2000) - Doria, José; Gasser, Hans-Peter; Bassiouni, M. Cherif, 1937-2017; Blishchenko, I. P. (Igorʹ Pavlovich) (International humanitarian law series ;, 2009)
This collection of essays covers important aspects of the legal regime of the International Criminal Court (ICC). The volume begins with an analysis of the historical development of the ICC.